Demographic and Economic Overview of the Corridor States : Punjab, Haryana, Uttar Pradesh, Bihar, Jharkhand and West Bengal - World Bank Group (Washington, DC, 2014)
Punjab, Haryana, Uttar Pradesh, Bihar, Jharkhand, and West Bengal, with their high concentration of population, agricultural productivity, and growing manufacturing activities are economically important for India. The construction of the corridor has the potential to increase inter-state connectivity as well as regional linkages with Bangladesh, Pakistan, and the port of Mumbai, which can in turn spur economic activity and regional integration. The purpose of this report is to provide an overview of demographic trends, human development indicators, and economic structure in the six states, as a preliminary repository of data and analysis. This report is intended to help identify detailed technical assistance, better inform policy priorities, and well-targeted investment decisions that leverage planned and ongoing infrastructure projects such as the corridor. The report is structured as follows: (1) introduction; (2) overview of the six corridor states encompassing urbanization, poverty, human development performance, and economic profiles; (3) state-level overview of demographic and economic development performance, disaggregated economic structure, and commodity movements; and (4) conclusion.